2020
DOI: 10.1177/0084672420917451
|View full text |Cite
|
Sign up to set email alerts
|

An authentic feeling? Religious experience through Q&A websites

Abstract: As the “Sacred Place”—meant as the new space for religions offered by the Internet—demands for continuous investigations on the encounter between traditional narratives and social practices, the rapid growth of Question and Answering websites asks for improving social research about the Authenticity of the religious feeling as well as their responsibility in the construction of a shared knowledge. In this background, the aim of this study is to investigate the role of Q&A websites as additional in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Through a continuous contamination between the religious and secular domains, between “religionese” ( Scardigno and Mininni, 2020 )—that is the language of religion—and common speech, positive and negative connotations, “up” and “down” attitudes, what is at stake in this homily is a kind of “egalitarianism” overcoming religious borders and belongings, including all human beings. As a matter of fact, the Pope almost bans the “I” subject pronoun in favor of the first person plural, so that the whole discourse is dotted with “we”: subjects and verbs, adjectives, and pronouns testify to his commitment in the several experiences and connotations of human belonging.…”
Section: The Researchmentioning
confidence: 99%
“…Through a continuous contamination between the religious and secular domains, between “religionese” ( Scardigno and Mininni, 2020 )—that is the language of religion—and common speech, positive and negative connotations, “up” and “down” attitudes, what is at stake in this homily is a kind of “egalitarianism” overcoming religious borders and belongings, including all human beings. As a matter of fact, the Pope almost bans the “I” subject pronoun in favor of the first person plural, so that the whole discourse is dotted with “we”: subjects and verbs, adjectives, and pronouns testify to his commitment in the several experiences and connotations of human belonging.…”
Section: The Researchmentioning
confidence: 99%
“…In addition, they have the opportunity to communicate and interact with friends and peers freely, due to the user's privilege to presume (produce and consume at the same time) opinions on social media. The most common social media such as Facebook, Twitter, and Instagram have shaped the narratives and practices of religious authority, religious identity, and religious community (Kgatle, 2018) where traditional offline religiosity is transformed through more subjective religious views and experiences (Campbell, 2012;Scardigno and Giuseppe, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The reflections from several recent studies have shown the use of social media as a multifunctional tool beyond the prevailing notion that social media is engaged merely for entertainment and information sharing (e.g., Kgatle, 2018;Tan Meng, 2019;Thomas et al, 2019;Hashmi et al, 2020;Scardigno and Giuseppe, 2020). Posting, sharing, liking, and commenting on religiosity have added to the functionality of social media such as creating online religious communities (Hashmi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations